Isoproterenol-Induced Permeability Transition Pore-Related Dysfunction of Heart Mitochondria Is Attenuated by Astaxanthin - Krestinin, Roman (Biomedicines, 2020)
Mitochondria are key organelles of the cell because their main function is the capture of energy-rich substrates from the cytoplasm and oxidative cleavage with the generation of carbon dioxide and water, processes that are coupled with the synthesis of ATP. Mitochondria are subject to oxidative stress through the formation of the mitochondrial permeability transition pore (mPTP). Various antioxidants are used to reduce damage caused by oxidative stress and to improve the protection of the antioxidant system. Astaxanthin (AST) is considered to be a dietary antioxidant, which is able to reduce oxidative stress and enhance the antioxidant defense system. In the present investigation, the effect of AST on the functional state of rat heart mitochondria impaired by isoproterenol (ISO) under mPTP functioning was examined. It was found that AST raised mitochondrial respiration, the Ca(2+) retention capacity (CRC), and the rate of TPP(+) influx in rat heart mitochondria (RHM) isolated from ISO-injected rats. However, the level of reactive oxygen species (ROS) production increased. In addition, the concentrations of cardiolipin (CL), Mn-SOD2, and the proteins regulating mPTP rose after the injection of ISO in RHM pretreated with AST. Based on the data obtained, we suggest that AST has a protective effect in rat heart mitochondria.